THE MAIN APPROACHES TO THE ANALYSIS AND IMPROVEMENT OF EFFICIENCY OF INNOVATIVE PROJECTS IN INDUSTRIALIZED COUNTRIES - K. I. Lugovtsev (Модернизация, инновация, развитие, 2016)
Methodical and organizational features characteristic to management of innovative projects and programs in industrially developed countries at federal and corporate levels are discussed. Differences in mechanisms of selection and stimulation of innovative projects and programs incomparison with domestic practice are defined.